Membrane structure in disease and drug therapy - Zimmer, G. (Guido), 1932- (Marcel Dekker, 2000)
This study asserts that cellular and intracellular membranes are active in every aspect of the body's physiology and pathophysiology. It compares secondary through to quaternary structures and protein sequences and guages their influence on health, disease and drug therapy.